2017
DOI: 10.4314/esa.v29i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic and health assessment of farmers’ multi-pesticide exposure

Abstract: Objective. This was a cross-sectional study conducted among 534 farmers in the largest vegetable -producing area in the northern part of the Philippines. This study assessed the ergonomic risk factors, and occupational health and safety conditions of farmers' multi-pesticide exposures.Methods. Methods consisted of interviewer-guided survey questionnaires on pesticide use among farmers, agricultural safety risk factors associated with pesticide exposure and physical health assessments of farmers. The subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The proportion of proper PPE use in our study population was 2% while the proportion of 'no PPE used' was 15%. The similar condition of low frequency of PPE use has been reported by several studies with agricultural workers in different countries [4,[19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 86%
“…The proportion of proper PPE use in our study population was 2% while the proportion of 'no PPE used' was 15%. The similar condition of low frequency of PPE use has been reported by several studies with agricultural workers in different countries [4,[19][20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 86%
“…The similar condition of low frequency of PPE use has been reported by several studies with agricultural workers in different countries. (4,(19)(20)(21)(22)(23)(24) Generally accepted that advising the use of PPE does not always result in adequate protection (25), so work practices come into play. Regarding the hygiene practices and spill treatment, we found that nearly all of our subjects reported having proper showering and changing clothes after spraying, just in agreement with the results from other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern in pesticide use was also commonly observed among other studies in the Philippines. 4,[15][16][17] In addition to this, it is also common practice among farmers to use one pesticide type and turn these into a cocktail mixture. 15,[17][18][19] Farmers do this due to their belief that mixing pesticides will have a synergistic effect, increasing their effectiveness among the produce.…”
Section: Discussionmentioning
confidence: 99%
“…Similar symptoms were also reported in other studies as well. 16,23,24,36 Another route of entry into the body for pesticides is through ingestion, which could occur through directly consuming the chemical or consuming contaminated food. An in-silico evaluation of pesticides showed that multiple pesticides registered with high intestinal absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation